Therapeutic Potential of Photosynthetic Microorganisms for Visceral Leishmaniasis: An Immunological Analysis - Vaitkevicius-Antão, Victor; Moreira-Silva, Jady; Reino, Isabelle Barreto da Silva Moreira; Melo, Maria Gabriella Nunes de; Silva-Júnior, José Noé da; Andrade, Alexsandra Frazão de; Araújo, Paulo Sérgio Ramos de; Bezerra, Raquel Pedrosa; Marques, Daniela de Araújo Viana; Ferreira, Silvana; Pessoa-e-Silva, Rômulo; Lorena, Virginia Maria Barros de; et al. (Frontiers in Immunology, 2022)
New therapeutic strategies for visceral leishmaniasis (VL) have been studied, and the development of an immunotherapeutic agent that modulates the host’s immune response is necessary. The aim of this study was to evaluate in vitro the bioactive extracts of photosynthetic microorganisms (PMs) for their leishmanicidal/leishmanistatic and immunomodulatory potentials. Bioactive extracts from PMs (Arthrospira platensis and Dunaliella tertiolecta) were obtained by sonication. Reference drugs, miltefosine (MTF) and N-methylglucamine antimoniate (SbV), were also evaluated. The selectivity index (SI) of treatments was determined by assays of inhibitory concentration (IC50) in Leishmania infantum cells and cytotoxic concentrations (CC50) in human peripheral blood mononuclear cells by the MTT method. The immune response was evaluated in healthy human cells by the production of cytokines and nitric oxide (NO) and the gene expression of Tbx21, GATA3, RORc, and FOXP3, using four concentrations (CC50, ½ CC50, ¼ CC50, and IC50) for in-vitro stimulation. Based on the data obtained, we observed that the extracts of D. tertiolecta (SI = 4.7) and A. platensis (SI = 3.8) presented better results when compared to SbV (SI = 2.1). When analyzing the immune response results, we identified that the extracts of PMs stimulated the production of cytokines of the Th1 profile more than the reference drugs. The extracts also demonstrated the ability to stimulate NO synthesis. Regarding gene expression, in all concentrations of A. platensis extracts, we found a balance between the Th1/Th2 profile, with the average expression of the Tbx21 gene more than the GATA3 in the highest concentration (CC50). Regarding the extract of D. tertiolecta, we can observe that, in the lowest concentrations, a balance between all the genes was present, with the average expression of the GATA3 gene being lower than the others. The best result was found in the ½ CC50 concentration, stimulating a balanced positive expression between the Th1×Th17×Treg profiles, with a negative expression of GATA3. Thus, PM extracts showed promising results, presenting low toxicity, leishmanicidal/leishmanistatic activity, and induction of the immune response, which could be potential therapeutic candidates for VL.